Satellite‐Detected Ocean Ecosystem Response to Volcanic Eruptions in the Subarctic Northeast Pacific Ocean. Issue 20 (18th October 2019) - Westberry, T.K.; Shi, Y.R.; Yu, H.; Behrenfeld, M.J.; Remer, L.A.
Abstract: Volcanic eruptions in the Aleutian Archipelago during the summer of 2008 deposited large quantities of iron‐laden ash to the subarctic North Pacific Ocean. The surface ocean ecosystem response has been previously characterized using limited in situ and autonomous field measurements and numerical modeling, but basin‐scale satellite remote sensing has been limited to a simple description of chlorophyll variability. Here, we show that the ecosystem response is a complex combination of phytoplankton biomass and physiology that can be described with satellite ocean color diagnostics such as the chlorophyll‐to‐carbon biomass ratio (Chl:Cphyto ) and chlorophyll fluorescence yield. Together, these quantities outline a more complete picture of ecological responses spanning unique signals of iron stress (and relief from), photoacclimation, changes in phytoplankton growth rate, increases in biomass, and timescales of decay for these processes. Plain Language Summary: Phytoplankton growth in nearly one third of the global ocean is limited by the micronutrient iron. Outside the influence of continental margins, the only mechanisms to introduce new iron to the surface ocean are mixing up from the deep ocean (such as during winter storms) and through airborne deposition of desert dust. However, every once in a while large volcanic eruptions can provide a temporary source of iron to the ocean through deposition of volcanic ash. The effects of this "fertilization" are nearly impossible to measure in the field because of the unpredictability of volcanic eruptions. Satellite platforms provide the necessary coverage for this scale of event but have been woefully underutilized to date. We revisit a pair of well‐documented volcanic eruptions from the Aleutian Archipelago and describe their impact on the surface ocean ecosystem of the subarctic North Pacific Ocean using novel satellite–derived products supplemented by model output. We are able to characterize the ecosystem response in terms of both increased phytoplankton growth and adjustments in their physiology. The latter is often neglected yet can be of equal or greater magnitude than changes in growth rate. Key Points: The ash deposition from Aleutian volcanic eruptions in 2008 provides a case study for remote sensing analyses of ocean ecosystem response Clear signals are seen in bulk satellite properties and phytoplankton physiological indices (Chl:C and chlorophyll fluorescence yield) Ocean ecosystem response to iron fertilization is complex and can only be characterized with multiple satellite remote sensing products